2010
DOI: 10.1021/jp101668n
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Incidence Diffraction and X-ray Reflectivity Studies of the Interactions of Inorganic Mercury Salts with Membrane Lipids in Langmuir Monolayers at the Air/Water Interface

Abstract: The interactions of mercury ions with the membrane phospholipids are considered to be of great importance regarding the toxicity of this metal in living organisms. To obtain deeper insight into this problem, we performed systematic studies applying the Langmuir technique complemented with synchrotron X-ray scattering methods (grazing incidence X-ray diffraction (GIXD) and X-ray reflectivity (XR)). We focused our attention on the interactions of inorganic mercury salts dissolved in the aqueous subphase with lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
1
22
2
Order By: Relevance
“…that is spread as a Langmuir monolayer (ML) at the vapor/solution (100 mM KCl and sub-mM FeCl 3 ) interface at low pH values at which the phosphate group is protonated, we employ surface sensitive X-ray diffraction and spectroscopic techniques [14][15][16][17][18][19] . Similar studies have been reported on various divalent ions with PC-based lipid monolayers albeit at relatively high salt concentrations (∼ 0.1 M; much higher than those in living cells), 20,21 showing changes in π − A isotherms but insignificant structural effects in the X-ray reflectivity or grazing incidence diffraction (GIXD). This is not surprising considering a recent moleculardynamic simulations that show strong competition between cation binding to PC and to water molecules.…”
Section: Introductionsupporting
confidence: 81%
“…that is spread as a Langmuir monolayer (ML) at the vapor/solution (100 mM KCl and sub-mM FeCl 3 ) interface at low pH values at which the phosphate group is protonated, we employ surface sensitive X-ray diffraction and spectroscopic techniques [14][15][16][17][18][19] . Similar studies have been reported on various divalent ions with PC-based lipid monolayers albeit at relatively high salt concentrations (∼ 0.1 M; much higher than those in living cells), 20,21 showing changes in π − A isotherms but insignificant structural effects in the X-ray reflectivity or grazing incidence diffraction (GIXD). This is not surprising considering a recent moleculardynamic simulations that show strong competition between cation binding to PC and to water molecules.…”
Section: Introductionsupporting
confidence: 81%
“…Frequency changes provide information about the molecular structure and interactions, whereas the quantitative evaluation of the measured band intensities allows the determination of the chain and group orientations. Grazing incidence X-ray diffraction provides information only about ordered domains within the monolayer [63,64], whereas specular X-ray reflectivity (XR) supplies access to the electron density distribution across the layer, allowing speculation about the monolayer profile constitution.…”
Section: General Principlesmentioning
confidence: 99%
“…With as little as 10 -7 M for Hg 2+ and 10 -8 M for Cd 2+ , these heavy metals were not only observed to expand the monolayer but C 1/2 values calculated (the metal ion concentration giving half of the maximum pressure change) showed a linear correlation between logarithms of C 1/2 values and logarithms of the acute lethal doses of the metal chlorides in rabbits or rats (Suzuki and Matsushita, 1969). Single component lipid monolayers of DPPG, DPPC, lyso-PC, and SM have also been utilized to observe interactions of Hg ions with membrane phospholipids (Broniatowski et al, 2010). In the presence of 500 μM HgCl 2 in the aqueous subphase, mercury ions were observed to interact more strongly to SM and lyso-PC monolayers.…”
Section: Heavy Metals and Neurotoxic Cations: Monolayersmentioning
confidence: 99%